"Metakaolin‐Slag‐Clinker Blends." The Role of Na+ or K+ as Alkaline Activators of Theses Ternary Blends. Issue 6 (11th May 2013) - Fernández‐Jiménez, Ana; Zibouche, Fatima; Boudissa, Nassima; García‐Lodeiro, Ines; Abadlia, Mohamed Tahar; Palomo, Angel
Abstract : This article reports on research into the use of solid alkalis (Na2 CO3 and K2 CO3 ) as activators to obtain hybrid cement (cement whose hydration generates a mix of C–A–S–H and (N, C)–A–S–H gels) from a blend of 20% clínker + 40% blast furnace slag + 40% metakaolin. More specifically, the study aimed to determine the effect of activator dosage (5 and 8 wt%) and type of alkaline cation (Na + or K + ) on the 2‐ and 28‐d mechanical strength of the end materials. The findings showed that the highest mechanical strength values were obtained with 5% Na2 CO3 . According to the XRD, NMR, and SEM/EDX analyses conducted on the reaction products, the alkalinity and solubilized chemical species generated by adding 5% Na2 CO3 to the system yielded a mix of (N, C)–A–S–H and C–A–S–H cementitious gels as the main reaction products. The secondary reaction products included metastable (3CaO·Al2 O3 ·CaCO3 ·11H2 O‐type) carboaluminates that evolved into the calcite or vaterite forms of calcium carbonate. When K2 CO3 was used (instead of Na2 CO3 ), a (3CaO·Al2 O3 ·0.5Ca(OH)2 ·0.5CaCO3 ·11H2 O‐type) hemicarboaluminate also formed. The study also revealed that Na + favors coagulation/precipitation more effectively than K +, generating gels with a wider range of Q n species.